Pengembangan Sistem Layanan Laundry berbasis Web (Studi Kasus: IIS Laundry Malang) - Alfin Martin Manurung; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
IIS Laundry is a laundry service in Malang City that still using manual system for ordering and managing order data. The order data that managed manually caused lost and exchanged clothes due to unclear handwriting on the invoice and IIS Laundry can be sued for the compensation. Manual archiving also carried the risk of losing data on orders that have been placed previously. Web-based laundry system is a solution to solve those problems for IIS Laundry.The system will solve the problems by making an online order that provides choice of services and clothes with an integrated invoice beetween the customer and IIS Laundry. Development of the system was carried out using waterfall software development model and object oriented approach. System was built using PHP programming language and MySQL as database management system. System has been tested using unit, integration, and validation testing strategy. Unit and integration testing have been done using white-box testing technique and validation testing has been done using black-box testing technique. The developed system from this research is expected to be able to help IIS Laundry in order to solve their problem..